Transport Network Analysis Of Kasaragod Taluk, Kerala Using GIS - R.V.VINOD, B. SUKUMAR, AHALYA SUKUMAR (INDIAN CARTOGRAPHER, 2003, 2003)
"Transportation is a measure of relations between areas and therefore an essential part of geography" (Ullman, 1954). Transport network development is considered to be one of the keys to rapid modernization and development, especially for better traffic efficiency. Other than the dense network of roads in cities, roads are often built in suburban areas to accelerate the development and economic growth of these areas. The study of the network includes an analysis of intersections (nodes), density of roads, and accessibility. The laying of roads are usually decided by political, social and economic factors, and it is not well balanced by natural conditions. As a consequence, problemsare often faced from rain, flood etc. Aim and objective of this paper is to study transport network of roads and railways in Kasaragod taluk, Kasaragod district of Northern Kerala. Kasaragod district was formed by the bifurcation of Kannur district for the purpose of effective implementation of developmental plans. The district has an area of 1961.30 sq. kms and a population for the district is 12,03,342 (2001 census). It has two taluks viz. Kasaragod and Hosdurg. The study area viz. Kasaragod taluk is the northern most taluk in the Kasaragod district as well as the Kerala State. The population of the taluk is 6,16,176 (2001 census). This constitutes 51 per cent of the population of the district. National High way No17 is passing through this district along the coast. Survey of India's topographic maps on 1:50,000 scale is used as base map and roads have been updated with IRS satellite imagery. Road network, nodes, connectivity density, and accessibility studies are made by using Map Info GIS software. The accessibility was derived from the buffer zonation. The density of roads nodes, connectivity and accessibility were compared with relief, drainage and population distribution. Panchayat boundaries are super imposed over the maps and relative positions of each Panchayat with reference to network of roads are studied to help the local self-government to develop the transportation network in the region. This will be useful for the planners in designing developmental projects for the region. From the analysis, it is found that the coastal area is well connected with road network and the eastern hilly region has poor connectivity and accessibility. Lack of bridges across rivers pose problem with connectivity of roads in the study area. Most of the roads run along east - west direction than north- south. Relief and drainage play dominant role in the road network development in the district